2018
DOI: 10.3390/ma11020198
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Properties of Laser Cladding Al-TiC-CeO2 Composite Coatings

Abstract: Al-TiC-CeO2 composite coatings have been prepared by using a laser cladding technique, and the microstructure and properties of the resulting composite coatings have been investigated using scanning electron microscopy (SEM), a 3D microscope system, X-ray diffraction (XRD), micro-hardness testing, X-ray stress measurements, friction and wear testing, and an electrochemical workstation. The results showed that an Al-Fe phase appears in the coatings under different applied laser powers and shows good metallurgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Rare earth oxides, some of the hottest modified materials used in the laser-cladding process, can not only optimize the microstructure and refine the grain, but can also improve fatigue, oxidation, wear, and corrosion resistance in various service environments [2][3][4][5]. This has resulted in laser cladding (using the modification of rare earth oxides) becoming a widely used coating preparation method [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth oxides, some of the hottest modified materials used in the laser-cladding process, can not only optimize the microstructure and refine the grain, but can also improve fatigue, oxidation, wear, and corrosion resistance in various service environments [2][3][4][5]. This has resulted in laser cladding (using the modification of rare earth oxides) becoming a widely used coating preparation method [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 shows EIS plots and fitting results of the PEO immersion coatings carried out in 3.5 wt % NaCl solution. The corrosion rate was different owing to the greater radius of the capacitive loop [ 33 , 34 ]; the larger the radius of the capacitive loop, the lower the corrosion rate of the coating. It can be seen from Figure 10 a that the coating exhibited high total impedance at the beginning of immersion, which indicated that the coating owned high corrosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…It demonstrates that the absolute values of the acoustic-elastic coefficients show a significant dependence on the scanning strategies used in the SLM forming process, and the mechanical properties of the specimen vary with the scanning strategy [27,45]. For the specimen whose mechanical properties are better, the absolute values of the corresponding acoustic-elastic coefficients were less.…”
mentioning
confidence: 92%